2020
DOI: 10.1016/j.dyepig.2020.108659
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of pyrimidine chromophores

Abstract: The large library of nonlinear optical (NLO) chromophores based on pyrimidine scaffold is discussed in this review. Since the first examples described thirteen years ago, the interest in pyrimidine push-pull NLO chromophores has increased dramatically, especially for second harmonic generation and two photon absorption. More than 130 properly selected chromophores are presented to demonstrate fundamental structure-property relationships and to highlight key applications of pyrimidine-derived materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 126 publications
0
23
0
Order By: Relevance
“…[173,174] Hydroxy pyrimidine was initially synthesized via solid-phase combinatorial chemistry approach using hydroxy acetophenones protected with Wang resin. The resin was reacted with aromatic aldehydes to form chalcones (12) for further cyclization (13). Deprotected hydroxy from the cleavage of Wang resin has produced pyrimidine derivatives (14) in 79%-93% yield.…”
Section: Homocyclic Pyrimidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[173,174] Hydroxy pyrimidine was initially synthesized via solid-phase combinatorial chemistry approach using hydroxy acetophenones protected with Wang resin. The resin was reacted with aromatic aldehydes to form chalcones (12) for further cyclization (13). Deprotected hydroxy from the cleavage of Wang resin has produced pyrimidine derivatives (14) in 79%-93% yield.…”
Section: Homocyclic Pyrimidinesmentioning
confidence: 99%
“…[12] and chromophore. [13] moiety due to their potential and applications in electrochromic, solvatochromic, optical, photochromic, [14] anti-corrosive, [15] chemosensor, [16] optoelectronics or organic light-emitting diodes, [17] and photoproduct of DNA. [18] In therapeutic industry, pyrimidine derivatives have also been reported to have a broad spectrum of biological properties, that is, anticancer, [19][20][21][22][23][24][25][26][27][28][29][30] antihistamine, [31,32] antinociceptive, [33] antilipase, [34] antifilarial, [35] antiparasitic, [36] antioxidant, [37,38] antituberculosis, [39,40] antihypertensive, [41] antimicrobial, [42][43][44][45][46][47] anticonvulsant, [48,49] antiallergic, [50,51] antipyretic, [52] anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The pyrimidine ring possesses a strong electron-deficient character [8] that can be advantageously used for fluorescent sensors, [9] OLED emitters [10] or two-photon chromophores. [7] Whereas 4-styrylpyrimidines bearing an electron-donating substituent exhibit relatively weak NLO response, [11] the optimization of the π-conjugated core between the pyrimidine and the donor group [12] and more importantly the methylation of pyrimidine [12,13] significantly enhance the NLO response. It has been also demonstrated that V-shaped 4,6-disubstituted pyrimidines exhibit more than 2times higher NLO response than their monosubstituted pyrimidine analogues.…”
Section: Introductionmentioning
confidence: 99%
“…The push‐pull structure consisting of an electron‐donating group linked to an electron‐withdrawing one via a π‐conjugated linker (D‐π‐A), leading to intramolecular charge transfer (ICT), is the typical design of second order NLO chromophores [6] . In this context, a large library of pyrimidine second order NLO chromophores has been developed [7] . The pyrimidine ring possesses a strong electron‐deficient character [8] that can be advantageously used for fluorescent sensors, [9] OLED emitters [10] or two‐photon chromophores [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation